Delivering Bad News Effectively. - Gemma Leigh Roberts, Dr (linkedin.com, 2017)
Discover how to confidently communicate bad news with tact and candor. Learn how to prepare to deliver bad news, manage the meeting itself, and then follow up to ensure clarity.